Comparative study of alternative equivalent frame approaches for the seismic assessment of masonry buildings in OpenSees. (1st May 2023) - Requena-Garcia-Cruz, M.V.; Cattari, S.; Bento, R.; Morales-Esteban, A.
Abstract: The equivalent frame (EF) idealisation of masonry structures is widely used in engineering structures. Despite its simplifications, reliable numerical models can be produced to calculate the seismic behaviour of unreinforced masonry (URM) buildings. Different EF modelling approaches have been implemented in commercial software specifically conceived for performing nonlinear analyses on URM buildings (such as 3Muri, adopted in this study). Furthermore, the adoption of such an approach is also possible in general-purpose structural analyses software packages, such as OpenSees, through an ad hoc implementation of analysts. The aim of this paper is to compare various EF modelling approaches by adopting alternative nonlinear beam-elements in OpenSees belonging to the distributed and the lumped plasticity. To this aim, the responses of some benchmark cases study available in the literature from the "URM nonlinear modelling-benchmark project" within the context of ReLUIS projects have been adopted to preliminary test the reliability of the alternative approaches considered. In particular, they consist of some single panels and a trilith, for which the results of various software are already available. In the paper, the results obtained with OpenSees have been more in-depth compared with 3Muri, which is assumed as representative of a larger set of EF models adopted in engineering-practice (having already verified in previous works that it provides a reasonable scatter with other software package options). Then, the analyses have been extended as well to a 3D building representative of the neighbourhood of 'El Plantinar' in Seville. An accurate comparison has been carried out in terms of generalised forces, drifts and damage at an element and at a global scale. The results have shown that the method proposed in this manuscript allows using OpenSees to calculate masonry structures with the EF approach with a good agreement to other engineering-practice oriented tools. Thus, this outcome may constitute, in future research, the basis for exploiting the potential and versatility of OpenSees in accounting for other tricky phenomena: the soil-foundation-structure interaction. Highlights: Comparison of EF modelling approaches for the seismic assessment of masonry buildings. Implementation, advantages and limitations of available EF modelling strategies are analysed. Alternative nonlinear beam-elements have been tested belonging to different plasticity approaches. Analyses have been extended to a 3D building representative of a neighbourhood in Spain. OpenSees can calculate masonry structures with EF-elements in good agreement with 3Muri.